Evaluation of the act synergistically to vitamin B12 with low-density lipoprotein LDL in the extender of the semen of Shami goats (Damascus University Journal of agriculture sciences, 2021)
The aim of this study was to evaluate the act synergistically to vitamin B12 with 8% LDL in the semen quality of male shami goats. Ten shami buck aged 3±1-year-old Shami goats were allocated to collect semen twice a week during the 2017 reproductive season, Several extenders were used, The first extender was sodium citrate with 8%LDL and was adopted as a local extender. In the other four extenders, Added to Local extender four different concentrations of vitamin B12 (1, 2, 3, 4 mg/ml). The sperm viability and plasma membrane integrity were assessed microscopically. The computer-assisted semen analysis (CASA) was also used to evaluate the sperm motility indices after thawing. The results showed that the percentage of viability and plasma membrane integrity sperm in the extender added to 2 mg/ml vitamin B12 was significantly superior (0.001>P) compared with the rest of the tested extenders. The average viability sperm after thawing was 77.07% and the plasma membrane integrity 75.67 % In the extender which 2 mg/ ml vitamin B12 was added compared to 70.44%, 72.43%, 57.00%, 57.57%; 68.45%, 70.57%, 55.80%, 54.14% in local extender, and extenders containing vitamin B12 (1, 3, 4, mg/ml), respectively. In motility MOT and progressive motility PROG (74.48%, 14.00% vs. 67.90%, 10.85%; 69.57%, 10.86%; 55.85%, 8.38%; 55.86% and 9.14% respectively), For the velocity of sperm, the extender supplemented with 2 mg/ml, exceeded (0.001>P) the other extenders in these indicators VAP, VCL and VSL (70.11 μm/s, 46.02 μm/s, 141.76 μm/s, respectively). It concluded that synergistic action between vitamin B12 and 8% LDL in the extender solution improved the quality of the sperm after freezing and thawing compared to the local extender, and the best concentration of vitamin B12 added to the extender was 2 mg/ml.
Keywords: Shami buck; Freezing